“Desarrollo de una aplicación móvil utilizando experiencia virtual 360 para la gestión de reservas y servicios del hotel Las Cascadas”. - Tuitice Valencia, Liliana Isabel (2023)
This research project focuses on the importance of technology in organizations to streamline processes and provide better services. Its main objective is to develop a mobile application to manage reservations and services at Las Cascadas Hotel. Android Studio and Java will use to create a native application that is compatible with Android devices. The database will develop in MySQL for high performance and security. In addition, images with a 360º virtual experience will include to improve the user experience. The Mobile D agile development methodology will use to guide the development process, and as a complement, a web application will create using Visual Studio Code to manage the mobile application. This project seeks to optimize the management of reservations and services in the hotel, providing an improved experience for both staff and customers through the use of appropriate technology and tools.